The determinants of occupational sorting: Evidence from Mozambique - Ines A. Ferreira; Sam Jones; Jorge Mouco; Ricardo Santos (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2021)
We examine the link between individual characteristics and sorting into different occupations using data from university students in Mozambique. We provide a comprehensive approach combining the main determinants of occupational sorting identified in the literature in a single framework to test both the importance and mutual independence of different groups of factors: fixed personal characteristics, job characteristics, economic preferences, and personality traits. We widen the typical scope of analysis by including the non-profit sector and selfemployment as alternative options to the public and private sectors, given their importance in the context of low-income countries. In line with previous work, we find that age and gender are important determinants of occupational choice. Our results give more weight to the importance of job characteristics as determinants of individuals' preferences compared to the effects of economic preferences and personality traits. We find a particularly surprising profile for those preferring the public sector, namely that they have a high propensity to cheat and a high score for neuroticism. Moreover, we do not find a significant effect of risk preferences or pro-sociality on the preference for this sector.
Keywords: C93; D91; J24; O12; 330; occupational choices; economic preferences; personal characteristics; Mozambique